Targeting Mitochondrial Network Architecture in Down Syndrome and Aging - Mollo, Nunzia (Int J Mol Sci, 2020)
Mitochondria are organelles that mainly control energy conversion in the cell. In addition, they also participate in many relevant activities, such as the regulation of apoptosis and calcium levels, and other metabolic tasks, all closely linked to cell viability. Functionality of mitochondria appears to depend upon their network architecture that may dynamically pass from an interconnected structure with long tubular units, to a fragmented one with short separate fragments. A decline in mitochondrial quality, which presents itself as an altered structural organization and a function of mitochondria, has been observed in Down syndrome (DS), as well as in aging and in age-related pathologies. This review provides a basic overview of mitochondrial dynamics, from fission/fusion mechanisms to mitochondrial homeostasis. Molecular mechanisms determining the disruption of the mitochondrial phenotype in DS and aging are discussed. The impaired activity of the transcriptional co-activator PGC-1α/PPARGC1A and the hyperactivation of the mammalian target of rapamycin (mTOR) kinase are emerging as molecular underlying causes of these mitochondrial alterations. It is, therefore, likely that either stimulating the PGC-1α activity or inhibiting mTOR signaling could reverse mitochondrial dysfunction. Evidence is summarized suggesting that drugs targeting either these pathways or other factors affecting the mitochondrial network may represent therapeutic approaches to improve and/or prevent the effects of altered mitochondrial function. Overall, from all these studies it emerges that the implementation of such strategies may exert protective effects in DS and age-related diseases.